2021
DOI: 10.3390/genes12020150
|View full text |Cite
|
Sign up to set email alerts
|

BARD1 Pathogenic Variants Are Associated with Triple-Negative Breast Cancer in a Spanish Hereditary Breast and Ovarian Cancer Cohort

Abstract: Only a small fraction of hereditary breast and/or ovarian cancer (HBOC) cases are caused by germline variants in the high-penetrance breast cancer 1 and 2 genes (BRCA1 and BRCA2). BRCA1-associated ring domain 1 (BARD1), nuclear partner of BRCA1, has been suggested as a potential HBOC risk gene, although its prevalence and penetrance are variable according to populations and type of tumor. We aimed to investigate the prevalence of BARD1 truncating variants in a cohort of patients with clinical suspicion of HBOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…We have recently published a case–control study investigating the role of BARD1 in cancer predisposition in a Spanish HBOC cohort of 4015 individuals. The results supported a significant association of BARD1 PVs with hereditary breast cancer (OR = 4.18; CI = 2.10–7.70; p = 5.45 × 10 –5 ), particularly among triple-negative tumors (OR = 5.40; CI = 1.77–18.15; p = 0.001) 28 . However, it should be noted that only truncating and canonical splice site variants were considered for the risk calculations, whose prevalence in breast and/or ovarian cancer cases is very limited.…”
Section: Discussionsupporting
confidence: 65%
“…We have recently published a case–control study investigating the role of BARD1 in cancer predisposition in a Spanish HBOC cohort of 4015 individuals. The results supported a significant association of BARD1 PVs with hereditary breast cancer (OR = 4.18; CI = 2.10–7.70; p = 5.45 × 10 –5 ), particularly among triple-negative tumors (OR = 5.40; CI = 1.77–18.15; p = 0.001) 28 . However, it should be noted that only truncating and canonical splice site variants were considered for the risk calculations, whose prevalence in breast and/or ovarian cancer cases is very limited.…”
Section: Discussionsupporting
confidence: 65%
“…Shimelis et al identified 25 individuals harboring BARD1 PVs (0.61%) and reported an OR of 5.92 for TNBC cases of African American and Caucasian populations [11]. Rofes et al identified ten BARD1 PV carriers from 680 TNBC patients (carrier frequency = 0.9%), resulting in an OR = 5.40 [60]. Similar observations were reported in other studies [61,62], indicating that BARD1 is a risk gene for TNBC.…”
Section: Tnbc and Non Brca-genessupporting
confidence: 54%
“…Previously, another study investigated the presence of germline PVs within the BARD1 gene in the Spanish population 17 . Among 4015 patients with clinical suspicion of HBOC, they identified 19 PVs: 8 truncating, 1 splicing and 2 large deletion, ending up with a PV prevalence of 0.47% which approximately doubles the 0.22% reported by Couch et al and the 0.25% described by Suszynska and Kozlowski 16 , 30 , and triples the 0.13% of protein-truncating variants reported by Dorling et al and the 0.15% identified by Hu et al 4 , 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Germline CNVs are recognized as the genetic cause of diverse hereditary pathologies, even though their detection via NGS is still challenging 32 . Only a few studies have characterized the CNV landscape within the BARD1 gene, having reported a total of 8 different large deletions so far in BC or OC patients 17 , 20 22 , 33 35 . In our study, we have detected the deletion of exon 1 and the deletion of the entire gene previously reported 20 , 21 and, what is more, we have identified for the first time exons 2–11, exon 9 and exons 10–11 deletions present in three BC cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation